Sexual intercourse among adolescent students of Santa Marta, Colombia: a cross-sectional survey. (Colombia Medica, 2007)
Background: Among teenagers, the prevalence of sexual intercourse (SI) varies from one country to another, and inside the same country, it varies from region to region. Information regarding SI in teenagers is unknown for a representative portion of students in Santa Marta, Colombia. Objective: To determinate the prevalence and factors associated with SI in middle-and high-school students from public and private schools from urban and rural zones. Method: A statistical sample provided by an anonymous survey done to a group of students. Logistic regression was used to control confounders associated with the fact of the student having had SI in his/her lifetime. Results: A total of 3,575 students, all grades and socioeconomic status, answered the survey. The mean age was 13.6 (SD=1.9), mean scholarship was 8.2 years (SD=1.6), and 57% were girls. A group of 804 (22.5%) students accepted having had SI. The having had SI was associated with being a boy (OR=8.5), alcohol drinking (OR=4.3), cannabis use (OR=4.2), cigarette smoking (OR=2.8), being older (OR=1.7), attending to private school (OR=1.3), and higher scholarship (OR=1.2). Conclusions: Twenty-five percent of the students reported having had SI. This is associated with unhealthy habits such as alcohol, cannabis and cigarettes consumption.